Connecting with and Distancing from: Transnational Influences in the Formation of Buddhist Identity and Practices in Bangladesh - Sraman, Upali (Journal of global buddhism, 2020)
The contemporary Theravāda form of Buddhism in Bangladesh was in fact introduced in 1856, following a reformation movement led by Sāramedha Mahāthera from the Arakan region of Burma. Following this reformation Bangladeshi Buddhists have connected with other Buddhist majority countries for models of Budddhist texts, religious practice, and education. Since the reformation, it has come to be mistakenly assumed that Bangladeshi Buddhists uniformly follow Theravāda Buddhism. In this paper, I clarify this misconception by pointing out that other forms of Buddhism are also practiced in Bangladesh. More specifically, the introduction of Mahāyana Buddhism through philanthropic organizations like Japan’s Rissho-Kōshei Kai also expand the transnational influences that shape Bangladeshi Buddhism. This requires us to reconsider scholarly assumptions on Bangladeshi Buddhism. As I sketch the outcomes of their transnational connections to survive in a Muslim majority country, I also examine how Myanmar’s Rohingya Muslim refugee crisis has put Bangladeshi Buddhists into a difficult situation, requiring them to distance from violent expressions of Buddhism.